Сценарии будущего в антропологической оптике - Функ, Дмитрий Анатольевич 1962- (Сибирские исторические исследования)
Рецензия на: Samimian-Darash, Limor. Uncertainty by design: preparing for the fu-ture with scenario technology. Ithaca [New York]: Cornell University Press, 2022. xv, 185 pp. ISBN 9781501762482 (pdf). Series: Expertise: cultures and technologies of knowledge